Multidimentional model in counseling to improve students’ self confidence - Sri Milfayetty (Universitas Negeri Padang, 2019)
There were some phenomen that the counselling for kinestetic student did not effective to improve their self confidence. The purpose of this study was to innovate the quality of counseling process through multidimentional model in improving students self confidence. The model was developed based on students’ self confidence. The method used research and development model of Borg and Gall. The procedures conducted were: i) premilinary survey to produce instrument to be used in assesing students’ need; (ii) designing counseling process; (iii) implementing and evaluating data were collected. The results indicated that the multidimentional model in counceling process could improve the students’ self confidence.